2009
DOI: 10.1017/s174217050800238x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Trichogramma ostriniae releases and habitat modification for suppression of European corn borer (Ostrinia nubilalis Hübner) in bell peppers

Abstract: A two-year field study was conducted to evaluate the effectiveness of Trichogramma ostriniae Pang et Chen (T.o.) releases in combination with habitat modification, to enhance biological control of European corn borer (ECB), Ostrinia nubilalis Hübner, the key pest of bell peppers in Kentucky. A randomized block design with a split-plot treatment arrangement was used in both years. Buckwheat, Fagopyrum esculetum Moench, was inter-planted as a nectar source for the wasps and as an attractant for ECB natural enemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…¡ Indicates released plots are significantly higher than intercropped plots, single DF contrasts, P < 0.050. resulted in $30% and 15% increase in parasitism of H. zea eggs over monoculture controls and intercropping corn with sunn hemp, respectively. A study comparing efficacy of T. ostriniae release to habitat modification (with inter-planting buckwheat) on parasitism of sentinel O. nubilalis eggs in bell peppers showed similar results, with higher parasitism in the release plots compared to buckwheat inter-planted and control plots (Russell and Bessin, 2009). Those results supported the findings of the current research, showing the augmentative biological control was more effective than conservation biological control with egg parasitoids.…”
Section: Parasitism Of H Zea Eggssupporting
confidence: 85%
See 1 more Smart Citation
“…¡ Indicates released plots are significantly higher than intercropped plots, single DF contrasts, P < 0.050. resulted in $30% and 15% increase in parasitism of H. zea eggs over monoculture controls and intercropping corn with sunn hemp, respectively. A study comparing efficacy of T. ostriniae release to habitat modification (with inter-planting buckwheat) on parasitism of sentinel O. nubilalis eggs in bell peppers showed similar results, with higher parasitism in the release plots compared to buckwheat inter-planted and control plots (Russell and Bessin, 2009). Those results supported the findings of the current research, showing the augmentative biological control was more effective than conservation biological control with egg parasitoids.…”
Section: Parasitism Of H Zea Eggssupporting
confidence: 85%
“…Previous studies have shown positive effects of Trichogramma releases on yields of various crops. For example, percentage of O. nubilalis infested bell pepper fruits was significantly less in plots receiving releases of T. ostriniae and buckwheat inter-planted plots compared to non-release and monoculture plots (Russell and Bessin, 2009). Similarly, inoculative releases of T. ostriniae significantly reduced plant and corn ear damage caused by O. nubilalis compared to non-release plots in sweet corn (Hoffman et al, 2006;Wright et al, 2002).…”
Section: Ear Yield and Quality Assessmentmentioning
confidence: 93%
“…), from extrafloral nectaries (Treacy et al 1987) and with buckwheat (Fagopyrum esculentum Moench), as the nectar source in both grape (Vitis spp.) (Nagarkatti et al 2003) and bell peppers (Capsicum annuum L.) (Russell and Bessin 2009;Sarajlić et al 2014). From these studies, sugar sources can significantly facilitate parasitism by Trichogramma wasps in the field as well as the laboratory.…”
mentioning
confidence: 99%
“…Flowering plants such as dill, coriander and buckwheat increased predation and parasitism of European corn borer, Ostrinia nubilalis (Hübner) (Lepidoptera: Crambidae) and aphids, with a significant increase in the populations of Orius spp., ladybeetle, damsel bugs (Nabidae), assassin bugs (Reduviidae) and hoverflies (Russell & Bessin 2009; Bickerton & Hamilton 2012). Intercropping with sweetcorn resulted in fewer cotton aphid, Aphis gossypii (Glover) (Hemiptera: Aphididae) with a significant increase in the abundance of ladybeetles and spiders (Idris & Roff 1999), whilst use of onion and garlic ( Allium sativum L.) (Amaryllidaceae) with capsicum significantly reduced the overall pest infestation and increased the yield by 51% and 44%, respectively (Aswathanarayanareddy et al .…”
Section: Global Habitat Management Workmentioning
confidence: 99%